Necessidades e demandas de informação dos técnicos da SEPLAN-MG - Marilia Vidigal Carneiro (1983)
Information needs and demands of the SEPLAN-MG technicians, their behavior at an information search and the performance of the CDP in attending the demands os their users were surveyed by means of a questionnaire which was sent to 175 technicians. The response rate of the questionnaire was 65,7%. The results showed a heavy use of statistical data, plans, programs, projects, and legislation. The most requested information sources are: reports, both internal and from other institutions, census, legislation and statistical data files. These sources are located, mainly, at the departaments files and at their personnel collections and files. The techinicians make a heavy use of oral communication to obtain the information required and most of the personal contacts are made inside SEPLAN. They attend the CDP to a frequency lower than monthly and there are a significant number of non-users. Solution to problems related to their work and search for documents are the reasons stated for going to CDP. Although they are not assiduous to the library, the techinicians stated they are satisfied with the CDP performance in attending their information requirements. A small number of techinicians use the library catalogue. Most of them ask for the librarian help when they go to the CDP. The most requested library services are local search, request by telephone and lending. Akthough using the library services less tahn monthly, most techinicians expresses considerable satisfaction with them. Suggestions are presented as contributions to CDP revision of its collection development policy and services offered to their users.